Efektifitas Konseling Seksual untuk Keharmonisan Keluarga Pasien Penyakit Ginjal Kronik Usia Produktif yang Menjalani Hemodialisis - Sarini Sarini; Linlin Lindayani; Arina Novilla; Yayat Suryati (Journal of Telenursing (JOTING), 2023)
The purpose of this study was to determine the effectiveness of sexual counseling on family harmony in productive age chronic kidney disease patients undergoing hemodialysis. This type of quantitative research uses a quasi-experimental study with a control group design where researchers provide sexual counseling interventions for family harmony in productive age chronic kidney disease patients undergoing hemodialysis. The results showed a p-value = 0.001 (p <0.05), which means that providing sexual counseling is effective for family harmony in productive age chronic kidney disease patients undergoing hemodialysis at Lira Medika Hospital, Karawang, West Java. In conclusion, sexual counseling has an effective effect on increasing family harmony Keywords : Family Harmony, Hemodialysis, Sexual Counseling